Entrepreneurship Opportunities in Electronic Physics Learning Media: A Literature Review - Anjani, Hilmi Rizki; Nilyani, Korry; Mufit, Fatni; Desnita, Desnita (Universitas Islam Negeri (UIN) Mataram, 2024)
Electronic physics learning is one of the rapidly growing fields in the current digital era. Electronic physical science learning media has turned into a compelling option in the growing experience. The point of this examination is to lead a writing survey on business venture potential to open doors in electronic material science learning media. Descriptive analysis is used as the research method, and secondary data is utilized. Entrepreneurship opportunities refer to the chance to run a profitable business. An entrepreneur needs to possess creative and innovative thinking, as well as the ability to take risks and seize business opportunities. Physics learning media is a tool used in the learning process to clarify the messages conveyed by teachers. Learning media that aligns with technological advancements, such as computer-based learning media and animations, can enhance students' interest in studying physics. Electronic-based learning (e-learning) utilizes information and communication technology for flexible learning, involving networks, learning support services, and tutor assistance. Through e-learning, students can learn anytime and anywhere. The development of digital media in e-learning can leverage the latest technologies, such as animations, Android-based applications, and augmented reality.